Anionic Surfactant Templated Hollow Silica Microspheres Containing Amino Groups for the Electrochemical Determination of Trace Lead (II). Issue 13 (1st January 2016) - Hao, He-Qun; Xie, Lei; Jin, Jun-Cheng; Wu, Ju; Xie, Cheng-Gen; Fu, Xu-Cheng
Abstract : In the paper, we developed a sensitive electrochemical sensor for the trace Pb(II) determination using hollow silica microspheres containing amino groups (NH2 -HSM) as a sensitive material. The NH2 -HSM was prepared by a direct co-condensation method, using sodium dodecyl sulfate (SDS) as an anionic surfactant template and the 3-aminopropyltrimethoxysilane (APTS) as a co-structure directing agent. The NH2 -HSM modified glassy carbon electrode (NH2 -HSM/GCE) showed a higher sensitivity and selectivity to Pb(II). The experimental conditions with respect to electrolyte, pH values and preconcentration time were optimized to maximize the sensitivity of the measurement. Under the optimized conditions, the linear response ranges for Pb(II) was 1.0–100.0 nM, with the corresponding detection limit was 0.5 nM (which is well below the guideline value given by the World Health Organization). In addition, the proposed sensor exhibited excellent repeatability and selectivity for Pb(II) over other relevant metal ions, thus can be further practical applied to determine Pb(II) in the real river water samples.